The (il)legality of the Iraq War of 2003: An Analytical Review of the Causes and Justifications for the US-led invasion - Nsama Jonathan Simuziya (Cogent Social Sciences)
This study aims to establish whether the 2003 Iraq war was waged within the confines of United Nations (UN) Charter rules. To achieve this, the study analyses the circumstances under which armed force in international relations (IR) may be used within the provisions of the UN Charter. In the wake of the contentious US-led war in Iraq, critics opine that the UN thresholds for waging war were not met by the US and its allies. The US argued that the war was justified given the unprecedented security challenges occasioned mainly by 9/11. Crucially, post 9/11, US re-ordering of international security fed on the narrative that preventative strikes against states that it suspected to be potential havens for terrorist activities (the so-called rogue states) was within the broader UN Charter parameters of self-defence. Using the UN Security Council Resolutions (SCRs) on Iraq and the UN Charter rules on warfare as a framework of analysis, this study navigates the causal factors and justifications for and against the Iraq war. The study concludes that although the US faced security challenges and arguably had fathomable reasons, the invasion of Iraq was conducted without UN authorisation, and hence in defiance of the UN Charter rules.